Minimal clinically important difference of the lower-extremity fugl–meyer assessment in chronic-stroke. Issue 4 (6th June 2016) - Pandian, Shanta; Arya, Kamal Narayan; Kumar, Dharmendra
Abstract: Background: The Minimal Clinically Important Difference (MCID), the smallest difference in the treatment outcome, augments both clinical and research practice. The MCID of the Fugl–Meyer assessment: Lower extremity (FMA-LE), an important motor measure in stroke, is not known. Objective: To estimate MCID score of FMA-LE using an anchor-based approach in chronic poststroke hemiparetic (>6 months) stroke subjects. Methods: Design: A prospective, observational study.Setting: Occupational therapy department of a rehabilitation institute.Participants: Sixty-five poststroke hemiparetic subjects (Mean age = 44.22 years, 42 men, Mean poststroke duration = 16.42 months).Intervention: The conventional motor therapy based on neurophysiological approaches was provided for the affected lower extremity (30 sessions, 45 min each, 3/week).Outcome Measures: FMA-LE, Functional ambulation classification (FAC), and global rating of patient-perceived changes (GRPPC).Result: The estimated MCID of FMA-LE was found to be a score of 6 using both FAC (sensitivity 90, specificity 94) and GRPPC (sensitivity 87, specificity 91).Conclusion: In chronic poststroke hemiparetic subjects, the computed MCID of FMA-LE is a score of 6. The subjects who achieve a change in a score of 6 on FMA-LE would perceive a meaningful recovery of lower-extremity function than those who do not. The reference value may be utilized in stroke rehabilitation.